Przezźreniczna termoterapia z iniekcjami octanu triamcinolonu pod tylną pochewkę Tenona w leczeniu wysiękowej postaci zwyrodnienia plamki związanego z wiekiem - Kubicka-Trząska, Agnieszka (Klinika Oczna / Acta Ophthalmologica Polonica, 2010)
Purpose: To evaluate the efficacy of transpupillary thermotherapy (TTT) with injection of triamcinolone acetonide under posterior Tenon’s capsule for exudative age-related macular degeneration (AMD). Material and methods: The study included two groups of patients with subfoveal choroidal neovascularization (CNV) due to AMD: group I (n = 20) received TTT alone and group II (n = 20) received TTT combined with sub-Tenon’s injection of 40 mg of triamcinolone acetonide (TA). The best corrected visual acuity (BCVA), Amsler grid test, contrast sensitivity and fluorescein angiography (FA) at 10-12 weeks after treatment were compared to the baseline values. Results: The average age for group I was 72.3 years and for group II 74.6 years. Occult CNV was present in 54% and 43%; predominately classic in 22% and 25%; and minimally classic in 24% and 32% of group I and II respectively. The baseline BCVA in group I ranged from 0.02 to 0.2 and in group II – from 0.03 to 0.1. BCVA was maintained or improved in 7 patients (35%) in group I and in 12 eyes (60%) in group II. The deterioration of the BCVA was noted in 13 patients (65%) and in 8 patients (40%) in group I and II respectively. In 65% of eyes in group I and in 83% in group II the improvement in contrast sensitivity was observed. The rate of color vision improvement was 62% and 91%. Regression of metamorphopsia and/ or scotoma in central visual field was observed in 11 cases (55%) and in 14 cases (70%) in group I and II respectively. FA showed complete or partial closure of CNV in 9 and 14 eyes (p = 0.02) in group I and II, respectively. Conclusions: The results of our preliminary study indicate that TTT combined with sub-Tenon’s injections of triamcinolone acetonide may be a beneficial treatment modality with tendency to better functional results than TTT alone, in patients with exudative AMD. However for the precise evaluation of efficacy of this therapy a larger group of patients and longer follow-up are necessary.